Lived Experiences of Social Studies Teachers Conducting Hybrid Classes amidst COVID-19 Pandemic - King Arnold C Satsatin; Jeoffrey C Latayan; Francisco P. Panopio Jr.; Sherwin B Sapin; John Frederick B Tesoro (Advanced Qualitative Research, 2023)
This phenomenological qualitative research study aimed to investigate the lived experiences of social studies teachers in a hybrid learning class amidst COVID–19 pandemic. There were five participants who were purposive and selected. Interviews were recorded, transcribed, and thematically analysed. Based on the findings, sixteen subthemes and four major themes emerged, and these are: Challenges in Hybrid Learning, Stability of Internet Connection, Necessary Support from Administration, and Coping Mechanisms of the Teachers. It was revealed that the teachers faced challenges in the delivery of hybrid learning classes, such as quality of equipment class, equipment, internet connectivity, preparation of instructional materials, and motivation techniques to be used in everyday classes. However, the school took action by providing basic computer equipment like speakers and headsets, internet providers and some materials they needed for teaching. In this new normal, flexibility, adaptability, adjustments, and considerations are needed based on how one understands, responds, and manages an ever-changing environment. It is recommended that the school administration intensify their assistance and provide high-quality equipment, complete materials and various trainings for their hybrid learning teachers. In online classes of hybrid learning, the teachers need to think of varied motivational techniques that will make the students active participants. Teachers may also need to attend webinars and training on the new strategies for conducting hybrid classes to enhance their skills in teaching online and face-to-face classes at the same time. Future researchers may conduct further studies using other research designs.